An integrated and centralized Umrah and Hajj management system - Nordin, Azlin; Samad, Elyas; Hisham-muddin, Fikri (IEEE Explore, 2025)
The annual Umrah and Hajj pilgrimages entail highly complex logistical arrangements to accommodate millions of pilgrims (jemaah) from diverse backgrounds. Due to limited familiarity with the environment and the overwhelming scale of the spiritual journey, many pilgrims become disoriented or lost, resulting in considerable distress and additional challenges for the travel agencies. To address these challenges, the Umroo project proposes a comprehensive system designed to address real-time location tracking, emergency communication, and streamlined pilgrimage management, enhancing the overall experience for all stakeholders involved. Using the Agile software development methodology, the system integrates all the requirements into two different platforms, which are (1) web-based application, and (2) mobile application. The Umroo in general (covers mobile app and web-based platforms) aims to enhance safety, communication, and the overall management of pilgrimage activities for pilgrims, mutawwifs, and travel agencies, while addressing challenges posed by network limitations.